Identifiying the Students’ Obstacles in Summarizing Descriptive Text - Samhudi (Enlightenment Publishing, 2024)
This study was conducted to find out the obstacles faced by students in summarizing descriptive text, and the factors that cause these obstacles. To obtain data in this study, the writer used two data collection techniques, namely questionnaire and interview. Questionnaire was used to know the students’ obstacles in learning summarizing text. Interview is intended to identify the causes of the students’ obstacles in summarizing descriptive text. The subjects of the study were six students in the eighth grade at SMPN 3 Nisam, two of whom had high academic achievement, two with medium academic achievement, and two with low academic achievement. The study's findings revealed that students had a variety of difficulties in summarizing descriptive text due to both internal and external factors. Internal challenges included poor sentence structure comprehension, in identifying key ideas of text and insufficient vocabulary mastery. External factors such as insufficient parental attention and support, limited opportunities for home-based English learning and practice, teacher teaching methods and a lack of supporting materials such as English reading materials and dictionaries were also identified as contributing to the students' obstacles in summarizing descriptive text.